2005
DOI: 10.1002/ca.20154
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate coursework in anatomy as a predictor of performance: Comparison between students taking a medical gross anatomy course of average length and a course shortened by curriculum reform

Abstract: The performance of students taking medical gross anatomy at the University of California at Davis during a 4-year period (1999-2002) was correlated with prior undergraduate anatomy coursework. Significant correlations were observed between class rank in medical anatomy and taking any undergraduate anatomy as well as the total number of undergraduate anatomy units (P<0.01). Taking human gross anatomy and an anatomy laboratory course were significantly correlated with medical anatomy class rank (P<0.01) as were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 7 publications
3
27
0
Order By: Relevance
“…The more knowledge and understanding of anatomy, embryology, and histology they take into the program with them, the better equipped they will be to survive the onslaught. As to whether this is really true, data are scarce; some support this seemingly logical premise, others do not (Rarey, 2001;Forester et al, 2002;Peterson and Tucker, 2005).…”
Section: Undergraduate Students Are Not Well Servedmentioning
confidence: 87%
“…The more knowledge and understanding of anatomy, embryology, and histology they take into the program with them, the better equipped they will be to survive the onslaught. As to whether this is really true, data are scarce; some support this seemingly logical premise, others do not (Rarey, 2001;Forester et al, 2002;Peterson and Tucker, 2005).…”
Section: Undergraduate Students Are Not Well Servedmentioning
confidence: 87%
“…These results are contrary to Forester et al (), which showed that students with any anatomy coursework performed significantly better than students without anatomy experiences. Peterson and Tucker () also showed that having taken any undergraduate anatomy had a positive correlation to final grade and class rank in medical gross anatomy when considering students in their longer, 172 hour, traditional course format. It should be noted that the final grade distribution for medical gross anatomy (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The American Dental Association (ADA) points potential applicants to the individual dental schools for requirements but again, anatomy is not listed (ADA, ). Even though students may not be required to take anatomy, prior course experience has been reported (Canaday and Lancaster, ; Forester et al, ; Peterson and Tucker, ; Kondrashov et al, ) but it is inconclusive as to the benefits gained from prior anatomy coursework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that students who take cadaverbased anatomy as undergraduates are better prepared for graduate work (Forester et al 2002, Peterson andTucker 2005). Increasingly, PUIs are offering programs in physician assistant science, athletic training, or sports and exercise science in which students do not go on to graduate programs, but obtain employment following graduation from their undergraduate institution.…”
Section: Benefitsmentioning
confidence: 99%